A68 IMPACT OF VIDEO CAPSULE ENDOSCOPY ON THE MANAGEMENT OF CHILDREN WITH GASTROINTESTINAL DISORDERS. (1st March 2018) - Ortiz, R; Deora, V; EL-MATARY, W
Abstract: Background: The impact of video capsule endoscopy (VCE) on the decision-making of clinical care for children with different gastrointestinal (GI) disorders is currently under-investigated. Aims: The aim of this study was to examine how VCE impacts the management of children with different GI disorders in real world clinical practice Methods: A retrospective chart review was performed for all consecutive children who under-went VCE at the Children's Hospital, Winnipeg, Manitoba from April 2012 to July 2016. Variables collected included any changes in diagnosis or treatment that took place based on VCE findings. Results: A total of 41 VCE studies for 37 children (median age 13 years, IQR = 10.5 – 15.5 years) with different GI disorders were included. There were changes in the diagnoses of 6 (15%) participants based on their VCE findings. Diagnostic categories included three children with inflammatory bowel disease (IBD), two participants with small bowel polyposis, and one with protein losing enteropathy secondary to primary intestinal lymphangiectasia. IBD was ruled out in 8 studies (20%) based on normal VCE. There were 12 studies (29%) where VCE resulted in meaningful changes in management including major changes in participants' treatment. VCE findings were discordant with findings from other small bowel imaging techniques in 15 (37%) studies. Conclusions: VCE is a useful tool with major impacts on clinical management of children with different GI disorders. Funding Agencies: None